The Analysis of the Notion of “Social-Economic Set-Up” - Александр Александрович Куракин (Journal of Economic Sociology, 2010)
The paper considers the possibility to investigate the economic life with the help of the notion of “social-economic set-up". The main statement is that social-economic set-up is not an independent theory but the continuation of other sociological theories. Any theory is an analytical block of definitions and notions. The concept of set-up is series of analytical blocks derived from the basic theoretical block. The author states that the concept of set-up could be applied to any sociological theory. The example of the construction scheme of the social-economic set-up on the basis of the Fligstein’s, Bourdieu’, Polanyi’s and Chayanov’s papers is given.